2021
DOI: 10.3390/su13031407
|View full text |Cite
|
Sign up to set email alerts
|

Soil Structure Stability under Different Land Uses in Association with Polyacrylamide Effects

Abstract: Soil structural stability is a vital aspect of soil quality and functions, and of maintaining sustainable land management. The objective of this study was to compare the contribution of four long-term land-use systems (crop, bush, grass, and forest) coupled with anionic polyacrylamide (PAM = 0, 25, and 200 mg L−1) application on the structural stability of soils in three watersheds of Ethiopia varying in elevation. Effect of treatments on soil structural stability indices were assessed using the high energy mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The CaCO 3 content is largely variable (~84%), with a mean value of 2.91%. Such variability of SOC, clay, and CaCO 3 is attributed to the distribution of parent material depending on the topography, elevation (e.g., change in temperature, precipitation, pH by elevation), and dissolution and leaching processes [2,60]. Among the M3 elements, Ca, K, and P were largely variable (~50%), and others varied moderately (20-40%).…”
Section: Reference Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The CaCO 3 content is largely variable (~84%), with a mean value of 2.91%. Such variability of SOC, clay, and CaCO 3 is attributed to the distribution of parent material depending on the topography, elevation (e.g., change in temperature, precipitation, pH by elevation), and dissolution and leaching processes [2,60]. Among the M3 elements, Ca, K, and P were largely variable (~50%), and others varied moderately (20-40%).…”
Section: Reference Datamentioning
confidence: 99%
“…The results suggested that the M3 elements are related to the variation in soil type or texture and basic soil properties (mostly CaCO 3 and pH), along with coexisting metals that can reliably assist as predictive factors [61]. Moreover, the role of CaCO 3 (e.g., Ca and electrolyte sources, and pH modifier) on soil biogeochemistry is still overlooked in mountain soils and needs greater attention for the monitoring of land degradation and quality [2,60]. Thus, for the current study, the tested soil properties can be formally categorized into two groups.…”
Section: Reference Datamentioning
confidence: 99%
See 2 more Smart Citations
“…5 mm in thickness, which prevents the removal of soil with water and wind [13]. For many years, polyacrylamide and copolymers of acrylamide with anionic monomers have been taken for soil stabilization [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%